Layout Effects on High Frequency and Noise Parameters in MOSFETs - Asmaa Nur Aqilah Zainal Badri; Norlaili Mohd Noh; Shukri bin Korakkottil Kunhi Mohd; Asrulnizam Abd Manaf; Arjuna Marzuki; Mohd Tafir Mustaffa (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
This study reviews related studies on the impact of the layout dependent effects on high frequency and RF noise parameter performances, carried out over the past decade. It specifically focuses on the doughnut and multi- finger layouts. The doughnut style involves the polygonal and the 4- sided techniques, while the multi-finger involving the narrow-oxide diffusion (OD) and multi-OD. The polygonal versus 4-sided doughnut, and the narrow-OD with multi-fingers versus multi-OD with multi- fingers are reviewed in this study. The high frequency parameters, which are of concern in this study, are the cut- off frequency (fT) and the maximum frequency (fMAX), whereas the noise parameters involved are noise resistance (RN) and the minimum noise figure (NFmin). In addition, MOSFET parameters, which are affected by the layout style that in turn may contribute to the changes in these high frequency, and noise parameters are also detailed. Such parameters include transconductance (Gm); gate resistance (Rg); effective mobility (μeff); and parasitic capacitances (cgg and cgd). Investigation by others has revealed that the polygonal doughnut may have a larger total area in comparison with the 4- sided doughnut. It is also found by means of this review that the multi-finger layout style with narrow-OD and high number of fingers may have the best performance in fT and fMAX, owing partly to the improvement in Gm, μeff, cgg, cgd and low frequency noise (LFN). A multi-OD with a lower number of fingers may lead to a lower performance in fT due to a lower Gm. Upon comparing the doughnut and the multi-finger layout styles, the doughnuts appeared to perform better than a standard multi-finger layout for fT, fMAX, Gm and μeff but are poorer in terms of LFN. It can then be concluded that the narrow-OD multi-finger may cause the increase of cgg as the transistor becomes narrower, whereas a multi-OD multi-finger may have high Rg and therefore may lead to the increase of fT and fMAX as the transistor becomes narrower. Besides, the doughnut layout style has a higher Gm and fT, leading to larger μeff from the elimination of shallow trench isolation (STI) stress.